POLA DYSMENORRHEA PRIMER PADA REMAJA DI MAN 1 SEMARANG - Ulfatul Mardhiyah; Ali Rosidi; Indri Astuti Purwanti (Universitas Muhammadiyah Semarang, 2015)
Menstruation is a sign of a primary sex for women. The most common menstrual disorders is dysmenorrhea. The average incidence of dysmenorrhea in Indonesia is about 55% of which consists of a primary dysmenorrhea (54.89%) and secondary dysmenorrhea (9.36%). Primary dysmenorrhea happened in MAN 1 Semarang as much as 27%. This research objects to describe the patterns of the primary dysmenorrhea in MAN 1 Semarang. The study was conducted by survey method and approach of cross-sectional. Respondents were selected X-grader is experiencing Dysmenorrhea. Sampling technique is simple random sampling and numbers of sample are 46 respondents. The results showed that most respondents always experiencing dysmenorrhea (65.2%), while respondents perceived dysmenorrhea symptoms are pain in the lower abdomen that extends to the back and leg (91.3%), sore on the leg (73.9 %), and sore at the waist (76.1%). Dysmenorrhea interval that occurred more than 3 years after menarche (47.8%) more than 2-3 years (39.1%) and less than 2 years (13%).Keywords: primary dysmenorrhea, menstrual disorder, teenager.